Impact of Shape and Total of Particle to Characteristics of Partial Discharge and Breakdown Voltage on Oil Insulation in Uniform Field - Daniar Fahmi; I Made Yulistya Negara; R. Wahyudi; Dimas Anton Asfani; Made Yudhi Setyawan; Mochammad Wahyudi (Department of Electrical Engineering ITS and FORTEI, 2018)
Oil insulation is one of the insulation medium types commonly used in high voltage apparatus. This insulation is to separate between the conductive part and non-conductive part. However, oil insulation can experience decreasing of dielectric strength. It may be caused by the presence of solid particles. Therefore, the testing was conducted to obtain the effect of solid particles to characteristics of partial discharge and breakdown voltage of oil insulation. The results generally proved that the existence of solid particles can reduce the breakdown voltage value of oil insulation. In addition, the solid particles led to two types of corona on oil insulation, namely positive and negative corona. Keywords: oil insulation; partial discharge; breakdown voltage; corona; particle shape; particle total.